Behind the Pork Sales Conflict: Intersection of Interests, Economic, and Public Policy in Medan City - Putri Zahra; Fitriani Fitriani (Al-Adyan: Journal of Religious Studies, 2026)
The conflict over pork sales in Medan represents a socio-religious issue that has emerged within a multicultural society as a result of the convergence of religious, economic, spatial planning, and public policy interests. This study aims to analyze the conflict resolution process in the pork sales case in Medan from the perspective of Johan Galtung by examining the elements of contradiction, attitude, and behavior, as well as the conflict resolution efforts undertaken by the stakeholders involved. This research employed a descriptive qualitative approach. Data were collected through semi-structured interviews with four key informants: the Chairperson of the Indonesian Ulema Council (MUI) of Medan, the Chairperson of the North Sumatra Regional Board of the Indonesian Christian Youth Movement (GAMKI), the Chairperson of the Medan Branch of GAMKI, and a representative of the Interfaith Harmony Forum (FKUB) of Medan. Data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings reveal that the conflict over pork sales was not solely driven by religious differences but also by competing interests related to economic activities, spatial planning, and government policies. From Johan Galtung's perspective, the conflict evolved through the interrelated dimensions of contradiction, attitude, and behavior. Conflict resolution was pursued through dialogue, mediation, interfaith communication, and collaboration among the government, religious leaders, civil society organizations, and the Interfaith Harmony Forum (FKUB). Nevertheless, the implementation of several agreements concerning the regulation of pork sales locations and policy certainty has yet to be fully realized. Therefore, strengthening communication, ensuring policy consistency, and fostering collaboration among stakeholders are essential prerequisites for achieving sustainable peace in a multicultural society. Konflik penjualan daging babi di Kota Medan merupakan salah satu persoalan sosial-keagamaan yang muncul di tengah masyarakat multikultural akibat pertemuan kepentingan keagamaan, ekonomi, penataan ruang, dan kebijakan pemerintah. Penelitian ini bertujuan menganalisis resolusi konflik atas kasus penjualan daging babi di Kota Medan menggunakan perspektif Johan Galtung dengan mengkaji unsur contradiction, attitude, behavior, serta upaya penyelesaian konflik yang dilakukan oleh para pihak. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui wawancara semi-terstruktur terhadap empat informan yang terdiri atas Ketua Majelis Ulama Indonesia (MUI) Kota Medan, Ketua DPD Gerakan Angkatan Muda Kristen Indonesia (GAMKI) Sumatera Utara, Ketua DPC GAMKI Kota Medan, dan Pengurus Forum Kerukunan Umat Beragama (FKUB) Kota Medan. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa konflik penjualan daging babi tidak semata-mata dipengaruhi oleh perbedaan keyakinan, tetapi juga oleh pertentangan kepentingan terkait aktivitas ekonomi, penataan ruang, serta kebijakan pemerintah. Berdasarkan perspektif Johan Galtung, konflik berkembang melalui keterkaitan unsur contradiction, attitude, dan behavior. Penyelesaian konflik dilakukan melalui dialog, mediasi, komunikasi lintas agama, serta kolaborasi antara pemerintah, tokoh agama, organisasi kemasyarakatan, dan FKUB. Namun, implementasi sejumlah kesepakatan mengenai penataan lokasi penjualan dan kepastian kebijakan masih belum terlaksana secara optimal. Oleh karena itu, penguatan komunikasi, konsistensi kebijakan, dan kolaborasi antarpemangku kepentingan menjadi prasyarat penting dalam mewujudkan perdamaian yang berkelanjutan di tengah masyarakat multikultural.